2021
DOI: 10.17061/phrp30012000
|View full text |Cite
|
Sign up to set email alerts
|

The impact of vicarious trauma on Aboriginal and/or Torres Strait Islander health researchers

Abstract: The trauma experienced by many Aboriginal and Torres Strait Islander women and their families in Australia affects the health and wellbeing of their communities • Little information is available on Aboriginal and/or Torres Strait Islander women researchers' experiences of vicarious trauma when conducting research in this area. There is also little guidance on how to safeguard the social and emotional wellbeing of the researcher or the research participants • We must consider the potential consequences for rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 5 publications
(5 reference statements)
0
13
0
Order By: Relevance
“…Despite the current lack of gold standards for trauma-informed research, this review identified recommendations in the literature for trauma research or research with trauma-exposed populations. These recommendations include using research for change (e.g., advocacy and de-stigmatization) [27, 31, 39-45, 49, 50, 56, 57, 60, 62, 64, 66, 68, 78, 84, 86-88, 90, 91, 95, 98, 101, 103, 135, 138, 174], centering agency and growth (e.g., assess and adapt to participants' needs for agency and safety in an ongoing manner, and provide appropriate support and resources) [27, 30, 31, 42-44, 51, 55, 61, 63, 67, 71-81, 90, 91, 93-95, 99-101, 136, 175], preparing and supporting researchers to process the impact of trauma connected to research [31,92,97,[102][103][104][105][106][107][108][109][110][111][112][113]176], and improving professional standards (e.g., study short and long-term effects of research participation, identify factors influencing research experiences, minimize the inclusion of trauma-affected control participants, and acknowledge meaningful predictors and intervention points) [23, 26, 27, 29-31, 65, 69, 74, 75, 77-81, 85, 93, 96, 115-119, 121-123, 125, 127, 128, 131, 133, 139, 146, 151, 154, 177]. We also identified needs for guidance and continued discussion pertaining to the design and conduct of research (e.g., how to use theory and how to define and investigate research populations), systemic issues (e.g., how to use multi-level frameworks and multi-dimensional understandings of trauma, and how to address systemic injustice), and research translation and applicability (e.g., how to translate findings widely and scale up evidence-based interventions, and how to impact policy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the current lack of gold standards for trauma-informed research, this review identified recommendations in the literature for trauma research or research with trauma-exposed populations. These recommendations include using research for change (e.g., advocacy and de-stigmatization) [27, 31, 39-45, 49, 50, 56, 57, 60, 62, 64, 66, 68, 78, 84, 86-88, 90, 91, 95, 98, 101, 103, 135, 138, 174], centering agency and growth (e.g., assess and adapt to participants' needs for agency and safety in an ongoing manner, and provide appropriate support and resources) [27, 30, 31, 42-44, 51, 55, 61, 63, 67, 71-81, 90, 91, 93-95, 99-101, 136, 175], preparing and supporting researchers to process the impact of trauma connected to research [31,92,97,[102][103][104][105][106][107][108][109][110][111][112][113]176], and improving professional standards (e.g., study short and long-term effects of research participation, identify factors influencing research experiences, minimize the inclusion of trauma-affected control participants, and acknowledge meaningful predictors and intervention points) [23, 26, 27, 29-31, 65, 69, 74, 75, 77-81, 85, 93, 96, 115-119, 121-123, 125, 127, 128, 131, 133, 139, 146, 151, 154, 177]. We also identified needs for guidance and continued discussion pertaining to the design and conduct of research (e.g., how to use theory and how to define and investigate research populations), systemic issues (e.g., how to use multi-level frameworks and multi-dimensional understandings of trauma, and how to address systemic injustice), and research translation and applicability (e.g., how to translate findings widely and scale up evidence-based interventions, and how to impact policy.…”
Section: Discussionmentioning
confidence: 99%
“…Researcher well-being. When studying trauma, researchers may experience participants' trauma vicariously, which could cause distress or burn-out [31,104]. Several authors offered recommendations to minimize distress and promote researcher well-being through self-care and addressing secondary traumatization.…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations